Lichtenstein Castle - Wallis, Robert, 1794-1878 (engraver):::Creator::::::::::::; Bartlett, William Henry 1809-1854 (artist):::Contributor::::::::::::
Color engraving of the Liechtenstein Castle with Vienna in the distance (?)